Pemberdayaan Ekonomi Pekerja Rokok Melalui Program Keterampilan Wirausaha untuk Meningkatkan Penghasilan Tambahan di Kecamatan Dawe Kudus - Suparjo; Mahda Kumala, Charisha; Adhi Dana, Yoga; Sri Sunarsih, Endang (Universitas 17 Agustus 1945 Semarang, 2025)
The cigarette industry in Dawe District, Kudus, has been the backbone of the local economy for decades. However, this heavy dependence on a single industrial sector creates economic vulnerability, especially when production fluctuations or policy changes affect the tobacco industry. An economic empowerment program through agricultural entrepreneurship skills is highly relevant in this context. Modern agriculture using wick hydroponic technology and mini Nutrient Film Technique (NFT) offers an appropriate solution because it has characteristics that are suited to the geographic and socioeconomic conditions of the Dawe community. This PKM program has proven that economic empowerment through technology and skills transfer can be an effective strategy for increasing community income. Based on the results achieved, it is recommended to replicate similar programs in other areas with similar characteristics. Furthermore, ongoing monitoring and evaluation are necessary to ensure the sustainability of the businesses pioneered by participants. Collaboration with relevant agencies and microfinance institutions can strengthen participants' access to capital for broader business development.